Aberrant Chromatin Remodeling by Retinoic Acid Receptor α Fusion Proteins Assessed at the Single-Cell Level - Qiu, Jihui (The American Society for Cell Biology, 2007)
Acute promyelocytic leukemia (APL) is characterized by specific chromosomal translocations, which generate fusion proteins such as promyelocytic leukemia (PML)-retinoic acid receptor (RAR)α and promyelocytic leukemia zinc finger (PLZF)-RARα (X-RARα). In this study, we have applied lac operator array systems to study the effects of X-RARα versus wild-type RARα on large-scale chromatin structure. The targeting of these enhanced cyan fluorescent protein-lac repressor-tagged RARα-containing proteins to the gene-amplification chromosomal region by lac operator repeats led to local chromatin condensation, recruitment of nuclear receptor corepressor, and histone deacetylase complex. The addition of retinoic acid (RA) induced large-scale chromatin decondensation in cells expressing RARα; however, cells expressing X-RARα, especially PML-RARα, demonstrated insensitive response to this effect of all-trans retinoic acid (ATRA). Although we did not reveal differences in RA-dependent colocalization of either silencing mediator for retinoid and thyroid or steroid receptor coactivator (SRC)-1 with RARα versus X-RARα, the hormone-independent association between SRC-1 and X-RARα on the array has been identified. Rather, compared with cells expressing RARα, fluorescence recovery after photobleaching of live transfected cells, demonstrated decreased mobility of SRC-1 on the X-RARα–bound chromatin. Thus, the impaired ability of APL fusion proteins to activate gene transcription in response to ATRA corresponds to their reduced ability to remodel chromatin, which may link to their ability to impair the mobility of key nuclear receptor coregulators.